Fusobacterium nucleatum facilitates proliferation and autophagy by activating miR-361-3p/NUDT1 axis through oxidative stress in hypopharyngeal squamous cell carcinoma - Hui-Ching Lau; Xiaohui Yuan; Huiying Huang; Ming Zhang; Chi-Yao Hsueh; Hongli Gong (BMC Cancer, 2023)
Abstract Background To investigate how Fusobacterium nucleatum (Fn) promotes oxidative stress and mediates proliferation and autophagy in hypopharyngeal squamous cell carcinoma (HPSCC). Methods The prognosis for 82 HPSCC cases was retrospectively analyzed. HPSCC cell line FaDu was co-cultured with Fn. Knockdown of NUDT1 (shNUDT1 group) was done after observing DNA damage response. CCK8 and tumorigenesis assays for proliferation observation, mitochondria ROS (MitoROS) measurement to examine intracellular oxidative stress, and ELISA to analyze concentration of 8-oxo-2’-deoxyguanosine (8-oxo-dG) in cells. Dual-luciferase reporter assays clarified miR-361-3p connection with NUDT1. Autophagy flow was observed using electron microscopy and related proteins. Results Fn was highly associated with NUDT1. The shNUDT1 group experienced lower proliferation compared with normal FaDu (NC group) in vivo and in vitro. The shNUDT1 group showed 8-oxo-dG and γH2AX to be elevated. Intracellular ROS decreased in shNUDT1Fn group when compared to Fn group. Upregulating miR-361-3p could suppress NUDT1 expression and downstream proliferation and autophagy. Fn modulated miR-361-3p via OH−, which could be proven by H2O2 assay and N-acetylcysteine. Conclusions Higher Fn in HPSCC patients suggests poorer prognosis. NUDT1 might affect cell proliferation and autophagy and modulate DNA damage response. The oxidative stress induced miR-361-3p/NUDT1 axis is first introduced in microbiome-carcinoma research.